The Case of TVG and TV3 on Instagram and Facebook: Exploitation of its Fiction Series as Transmedia Content - Sinde Stompel, Roberto; Brito Lorenzo, Diego; González Grimon, Sima (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Derived from the crisis of the public service system in all areas and mainly the case of television, and under the premise of focusing on the shortcomings and possibilities that must be faced in the process of digitalization of society and consumption of audiovisual content, in this study the Spanish regional channels TVG and TV3 will be analyzed in the exploitation of their fiction series and mainly the transmedia carried out by them through their social networks; Facebook and Instagram.